2005
DOI: 10.1080/09715010.2005.10514806
|View full text |Cite
|
Sign up to set email alerts
|

Manning's Roughness Coefficient in Alluvial Channels Affected by Seepage

Abstract: Seepage flow through alluvial channel bed can affect significantly the Manning's roughness coefficient, n. Both downward seepage (suction) and upward seepage (injection) through the alluvial channel bed can either increase or decrease Manning's n when compared to its no-seepage value. Such variations in Manning's n due to seepage are presented quantitatively so as to bring awareness among design engineers and researchers that seepage should be considered as a parameter while estimating the value of Manning's n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…The present theoretical and experimental investigations [13], [34], [35], [6] do not give an unequivocal answer to the question about the effect of seepage flow on the main flow. Chen and Chiew [34] showed that the customarily used law of the wall (logarithmic law) is also not applicable to open channel flow subjected to bed suction.…”
Section: Resistance Equation At Incipient Motion With and Without Seementioning
confidence: 99%
See 1 more Smart Citation
“…The present theoretical and experimental investigations [13], [34], [35], [6] do not give an unequivocal answer to the question about the effect of seepage flow on the main flow. Chen and Chiew [34] showed that the customarily used law of the wall (logarithmic law) is also not applicable to open channel flow subjected to bed suction.…”
Section: Resistance Equation At Incipient Motion With and Without Seementioning
confidence: 99%
“…Chen and Chiew [34] showed that the customarily used law of the wall (logarithmic law) is also not applicable to open channel flow subjected to bed suction. Sitaram and Rao [35] have ascertained that Manning's n values are significantly affected from the seepage, thus there is a need to have a different kind of equation. Hence it has become necessary to develop a new resistance equation for plane sediment beds affected by bed suction.…”
Section: Resistance Equation At Incipient Motion With and Without Seementioning
confidence: 99%